Distribution And Diversity Of Zooplankton As Bioindicator Of Water Quality Status In Air Itam Reservoir, Penang, Malaysia - Sari, Intan (2009)
Zooplankton composition and abundance, and water quality parameters were studied in Air Itam Reservoir from May 2006 to February 2007. This study investigates the community structure of zooplankton as indicators of water quality of the reservoir, which was constructed for domestic water supply. Zooplankton was sampled with a Wisconsin plankton net of 80 μm mesh size, from five meters vertical intervals. Physicochemical parameters used as the indicators of water quality were dissolved oxygen (DO), temperature, pH, biological oxygen demand (BOD), chemical oxygen demand (COD), conductivity, nitrates, nitrites, orthophosphates, total suspended solids (TSS), total dissolved solids (TDS), water transparency and total coliform bacteria.